Hypotheses, rationale, design, and methods for prognostic evaluation of a randomized comparison between patients with coronary artery disease associated with ischemic cardiomyopathy who undergo medical or surgical treatment: MASS-VI (HF) - Paulo Cury Rezende; Whady Hueb; Edimar Alcides Bocchi; Michael Farkouh; Carlos Vicente Serrano Junior; Eduardo Gomes Lima; Expedito Eustáquio Ribeiro Silva; Luis Alberto Oliveira Dallan; Fabio Antonio Gaiotto; Cibele Larrosa Garzillo; Carlos Eduardo Rochitte; Cesar Higa Nomura; et al. (Trials, 2020)
Abstract Background Ischemic cardiomyopathy and severe left ventricular dysfunction are well established to represent the main determinants of poor survival and premature death compared with preserved ventricular function. However, the role of myocardial revascularization as a therapeutic alternative is not known to improve the long-term prognosis in this group of patients. This study will investigate whether myocardial revascularization contributes to a better prognosis for patients compared with those treated with drugs alone and followed over the long term. Methods The study will include 600 patients with coronary artery disease associated with ischemic cardiomyopathy. The surgical or drug therapy option will be randomized, and the events considered for analysis will be all-cause mortality, nonfatal infarction, unstable angina requiring additional revascularization, and stroke. The events will be analyzed according to the intent-to-treat principle. Patients with multivessel coronary disease and left ventricular ejection fraction measurements of less than 35% will be included. In addition, myocardial ischemia will be documented by myocardial scintigraphy. Markers of myocardial necrosis will be checked at admission and after the procedure. Discussion The role of myocardial revascularization (CABG) in the treatment of patients with coronary artery disease and heart failure is not clearly established. The surgical option of revascularizing the myocardium is a procedure designed to reduce the load of myocardial hibernation in patients with heart failure caused by coronary artery disease. On the other hand, the assessment of myocardial viability is frequently used to identify patients with left ventricular ischemic dysfunction in which CABG may add survival benefit. However, the effectiveness of this option is uncertain. The great difficulty in establishing the efficacy of surgical intervention is based on the understanding of viability without ischemia. Thus, this study will include only patients with viable and truly ischemic myocardium to correct this anomaly. Trial registration Evaluation of a randomized comparison between patients with coronary artery disease associated with ischemic cardiomyopathy submitted to medical or surgical treatment: MASS-VI (HF), ISRCTN77449548 , Oct 10th, 2019 (retrospectively registered).